The ability of Ex2Box4+ to interact with guests containing π‐electron‐rich and π‐electron‐poor moieties. Issue 15 (16th February 2018) - Nagurniak, Glaucio R.; Caramori, Giovanni F.; Muñoz‐Castro, Alvaro; Parreira, Renato L. T.; da Silva, Éder H.
Abstract: The ability of Ex2 Box 4+ as a host, able to trap guests containing both π‐electron rich (polycyclic aromatic hydrocarbons‐PAHs) and π‐electron poor (quinoid‐ and nitro‐PAHs) moieties was investigated to shed light on the main factors that control the host–guest (HG) interaction. The nature of the HG interactions was elucidated by energy decomposition (EDA‐NOCV), noncovalent interaction (NCI), and magnetic response analyses. EDA‐NOCV reveals that dispersion contributions are the most significant to sustain the HG interaction, while electrostatic and orbital contributions are very tiny. In fact, no significant covalent character in the HG interactions was observed. The obtained results point strictly to NCIs, modulated by dispersion contributions. Regardless of whether the guests contain π‐electron‐rich or π‐electron‐poor moieties, and no significant charge‐transfer was observed. All in all, HG interactions between guests 3‐14 and host 2 are predominantly modulated by π‐π stacking. Abstract : Ex2 Box 4+ is able to trap guests containing both π‐electron rich and π‐electron poor moieties. The results point strictly to host–guest interactions are mainly noncovalent (dispersion) and no significant charge‐transfer is observed.